Differences in underpricing of A-REIT IPOs and Australian property company IPOs. Issue 2 (7th March 2016) - Dimovski, Bill
Abstract : Purpose: – A variety of papers have analyzed the underpricing of REIT IPOs or property company IPOs. The purpose of this paper is to compare the two sectors and examines differences in the underpricing of the two types of IPOs. Design/methodology/approach: – An OLS regression is used to identify factors influencing the underpricing of A-REIT and property company IPOs from 1994 until 2014. Findings: – This study finds that A-REIT IPOs have a significantly lower underpricing on average than Australian property company IPOs. The time taken to list appears to influence the underpricing of both A-REIT IPOs and property company IPOs, in that issues that are filled more quickly have higher underpricing but with the magnitude of the impact being less for A-REITs. The sentiment toward the stock market also appears to impact on the underpricing of A-REIT and property company IPOs again with the magnitude of the impact being less for A-REITs. Practical implications: – The paper provides information to new A-REIT and property company issuers, underwriters and investors. Originality/value: – The study is the first to compare and examine the differences in the underpricing of both REITs and property companies in the one country over the same time period.